(3GdJPcQI aj Ydhe GdMOjKs - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s
(3ChdgG (B:s
(3agPg JPcQI ai Ydhe GdMOjK s
(3BNQgG (B:s
(3aQZJ ef JMQjQ gPg GdJPcQI ai fMh SGYJjf ef UHjMI jhe GdLeYI SGHY YTQ LeGOi GdChdi SfI KdGK hSJjf hSHYeGFIq s
(3Vef eLehY , JQJjHgG (B: 4s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B57s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B392s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs